Analisis Kepatuhan Penggunaan Alat Pelindung Diri (APD) Perawat Instalasi Gawat Darurat (IGD) Terhadap Keselamatan Kerja Di RSUD Marthen Indey Jayapura - Sri Nurindasari; Fhirawati; Fausiyah Annisa; Didik Mahawijaya (Window of Public Health Journal, 2025)
Nurse compliance in using PPE is professional behavior towards a recommendation, procedure, or regulation that must be obeyed. Low behavior towards the use of PPE can be fatal to the safety and health of nurses. This study aims to provide an overview of compliance with the use of PPE on the occupational safety of emergency room nurses at Marthen Indey Jayapura Hospital. This study uses a descriptive study design with cross-sectional observations. The sample used was all nurses who worked in the emergency room of Marthen Indey Hospital Jayapura as many as 30 people. This study using univariate analysis obtained the following results: The characteristics of the respondents in this study were the age category in early adulthood (26-35 years) as many as 21 people (70%), the majority of male gender as many as 17 people (56.7%), the majority of nurses working ≥ 3 years as many as 24 people (80%). Nurses' knowledge of PPE was in the good category for as many as 27 people (90%). PPE at Marthen Indey Hospital is classified as available according to nurses, with as many as 30 nurses (100%). Notably, nurses' compliance with the use of PPE in the emergency room of Marthen Indey Hospital was classified as compliant among as many as 21 people (70%), indicating a high level of safety measures in place.